Comparison of real-time PCR, conventional PCR and RT-lamp for the detection of Coconut Cadang-Cadang Viroid variant in oil palm - Roslan, Nur Diyana; Vadamalai, Ganesan; Idris, Abu Seman; Kong, Lih Ling; Sundram, Shamala (Malaysian Palm Oil Board, 2023)
Real-time quantitative polymerase chain reaction (real-time PCR) was designed for the detection of oil palm Coconut Cadang-cadang Viroid (CCCVd) 246 nt variant. The primers and probe specifically designed for the real-time PCR were optimised with 300 nM of probe against a primer concentration of 400 nM for the detection of oil palm CCCVd variants. Oil palm CCCVd 246 nt variant was successfully detected using realtime PCR in leaf samples collected from 14 symptomatic oil palm from various regions. The sensitivity of real-time PCR was compared with reverse transcription loop-mediated isothermal amplification (RT-LAMP) and conventional PCR. The latter two techniques were reported earlier to be able to detect CCCVd variants in oil palm. Conventional PCR analysis using CCCVd full-length primers detected the presence of CCCVd 246 nt variant in 10 while RT-LAMP detected only seven positive samples from the total 14 field samples. The real-time PCR was highly sensitive and reliable compared to the two detection techniques. The primers designed for the real-time PCR were specific as only the oil palm CCCVd variant plasmid was detected with high fluorescence and lowest quantification cycle (Cq value) compared to the other tested viroids (ASSVd, CTiVd, ELVd, HLVd and PLMVd). The present study has proven the reliability of the technique, thus, highly recommending the next step of developing the high-throughput diagnostic procedure for the eventual use in epidemiological monitoring programmes.